Self-Regulated Learning for Vocational Students’ Inductive Thinking in Solving Contextual Geometric-Sequence Problems - Sari, Ragista Maya; Nurcahyo, Adi; Swastika, Annisa (Jurnal VARIDIKA, 2026)
Contextual problems play an important role in learning in vocational high schools because they connect mathematical concepts with real-life situations relevant to students. However, studies that specifically examine vocational high school students’ inductive thinking skills in solving contextual mathematical problems, particularly in geometric sequences, viewed from the level of Self-Regulated Learning (SRL), are still limited. This study aims to analyze the inductive thinking abilities of vocational high school students in solving contextual geometric sequence problems based on their SRL levels. A qualitative approach with descriptive analysis was employed. The research subjects consisted of 33 eleventh-grade students from the Accounting and Institutional Finance class at SMK Negeri 1 Boyolali. The results showed that 3 students were categorized as having high SRL, 24 students had moderate SRL, and 6 students had low SRL. Analysis of students’ responses revealed that students with high SRL were able to meet all indicators of inductive reasoning, namely observing regularities, identifying patterns, and formulating generalizations. Students with moderate SRL were able to observe regularities and identify patterns but experienced difficulties in formulating generalizations. Meanwhile, students with low SRL were only able to observe regularities. These findings indicate that SRL levels influence students’ inductive thinking abilities. This research revealing students’ characteristics and difficulties at each inductive reasoning indicator based on SRL levels within the context of geometric sequences in vocational high schools, as well as providing practical implications for teachers in designing more effective contextual mathematics learning.